Deepfake as a New Form of Cybercrime: Evaluating the Adequacy of Indonesian Criminal Law in Protecting Digital Society - Sri Ayu Astuti (PT. Anagata Sembagi Education, 2026)
The rapid diffusion of generative artificial intelligence has made deepfake technology a low-cost instrument for fraud, defamation, non-consensual pornography, sextortion, identity misuse, and political disinformation, yet Indonesia has no criminal provision that names “deepfake” as a distinct offense. This article evaluates the adequacy of Indonesian criminal law in protecting digital society against deepfake-enabled cybercrime. The analysis maps how the ITE Law, the Penal Code, the Personal Data Protection Law, and the Pornography Law are stretched to reach deepfake conduct, identifies the harm categories most frequently reported in the literature, and evaluates enforcement capacity, victim protection, and reform proposals. The findings show that Indonesian positive law remains reactive, fragmented, and interpretively strained, lacking an explicit statutory definition of deepfake, a lex specialis offense, adequate digital forensic capacity, and coordinated platform accountability mechanisms. The article concludes that legal adequacy cannot be achieved through criminalization alone and proposes a multi-layered reform agenda combining statutory reform, forensic capacity building, platform and labeling obligations, and digital literacy programs.